(untitled) (Fiep Bulletin - online, 2012)
The article presents a series of relevant events and studies that have emerged in the last 20 years andcorrelates them to the current situation and tendencies of sports and physical education. It stems from acontextual analysis of the evolution of Physical Education and Sports starting from Western Physical Educationdoctrines, going through the surge of Physical Education for Adults and the contribution made by the Young MenChristian Association, which spread this practice. It goes on describing the “Sports for All” movement, which,among others, democratized the sports practices and included Sports as every individual’s right in reformulatedConstitutions. It also mentions the important role played by sports international organizations, as FIEP, in theorganization and reference for sports practice in the transition from the 20th to the 21st centuries.Among many Physical Education tendencies that derive from Agenda 21 and FIEPWorld Manifesto ofthe Physical Education 2000 are: (1) the expansion of Physical Education limits beyond school environment; (2)the binding between the denomination of physical education to the educational intention of the sports practice; (3)the role of sports as an instrument for inclusion and fight against social inequalities and others. The trends for theSports are: the emergence of new sports modalities; the increase of labor fields for the sports professionals; theemergence of new scientific specializations related to sports; the appearance of new scientific specializationsconnected to sports, the dependence of sports rules on the media needs, among other facts.Key words: Sports for All, FIEPWorld Manifesto of the Physical Education 2000, Agenda 21.